Women’s Choice of Immediate Postpartum Reversible Contraceptives Visiting a Tertiary Hospital of Nepal - Shrestha, Subha; Shrestha, Buddhi Kumar; Shrestha, Rubina; Upadhyay, Hari Prasad; Poudel, Sneha (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Long-acting reversible contraceptives (LARC, Intrauterine contraceptives devices and Implants) stand on 1st regards to safety and effectiveness. It is an easily accessible variety for spacing birth as well as preventing unintended pregnancy soon after childbirth in Nepal due to free supply by the Government under safe motherhood program of Reproductive health policy. Despite free supply, LARC is not routinely implemented in practice among immediate post-partum lady as single approach contraceptives concern to unintended pregnancy due to unmet need. To find out the choice of LARC by antenatal and immediate postpartum women after delivery. Methods: A descriptive cross-sectional study was conducted among 200 women in antenatal clinic and obstetric ward of College of Medical Science and Teaching Hospital using non probability convince sampling technique. Ethical approval was taken form Institutional Review Committee of College of Medical Sciences and Teaching Hospital and data was analyzed using descriptive statistical tools in SPSS. Results: Twenty eight percent of antenatal and 42% of postnatal women had induced abortion for unintended pregnancy in past. All women had knowledge about modern method of contraception but only 47 percent antenatal and 58 percent postnatal women adopted contraception in past. Implant was chosen by 44% antenatal and 46% postnatal women; whereas IUCD was chosen by 45% antenatal and postnatal women as LARC. Jadelle was the choice of LARC in both group due to its convenient duration (5 years) for birth spacing and its safety profile during breastfeeding. Twenty women refuse for LARC in immediate postpartum period. Conclusions: Single approach immediate postpartum LARC in is chosen by women who had induced abortion for unintended pregnancy in past for its long action, convenience during breast feeding and reliability. Maximum antenatal women prefer IUCD compared to Implants among postnatal women. Keywords: Copper T; Immediate post-partum; Jadelle; long-acting reversible contraceptives; Puerperium; Unintended pregnancy.